2001
DOI: 10.1111/j.1365-2427.2001.00628.x
|View full text |Cite
|
Sign up to set email alerts
|

Variability in stream macroinvertebrates at multiple spatial scales

Abstract: 1. We intensively sampled 16 western Oregon streams to characterize: (1) the variability in macroinvertebrate assemblages at seven spatial scales; and (2) the change in taxon richness with increasing sampling effort. An analysis of variance (ANOVA) model calculated spatial variance components for taxon richness, total density, percent individuals of Ephemeroptera, Plecoptera and Trichoptera (EPT), percent dominance and Shannon diversity. 2. At the landscape level, ecoregion and among-streams components dominat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(36 citation statements)
references
References 41 publications
3
33
0
Order By: Relevance
“…In particular, our findings are based on observations from a single river, hindering generalisations at larger spatial scales Probability is reported as **B0.05; **B0.01; ***B0.001; ns C 0.05 Hydrobiologia or across different eco-regions. Also, the different levels of resolution at which invertebrates were identified (species, genus, family) could have potentially limited our ability to quantify community variation, especially over small spatial gradients such as the micro-habitat scale (Li et al, 2001;Heino et al, 2004). Nonetheless, as explained in the introduction, the Aniene river is a fair representative of many Apennine rivers in central Italy that show similar longitudinal gradients.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, our findings are based on observations from a single river, hindering generalisations at larger spatial scales Probability is reported as **B0.05; **B0.01; ***B0.001; ns C 0.05 Hydrobiologia or across different eco-regions. Also, the different levels of resolution at which invertebrates were identified (species, genus, family) could have potentially limited our ability to quantify community variation, especially over small spatial gradients such as the micro-habitat scale (Li et al, 2001;Heino et al, 2004). Nonetheless, as explained in the introduction, the Aniene river is a fair representative of many Apennine rivers in central Italy that show similar longitudinal gradients.…”
Section: Discussionmentioning
confidence: 99%
“…Gresswell et al (2006) found that nested spatial variation in the relative abundance of coastal cutthroat trout in their variograms displayed the degree of spatial autocorrelation among samples. Peterson (Labbe and Fausch 2000;Li et al 2001;Thompson et al 2001;Fausch et al 2002;Durance et al 2006) reveals that the relative importance of ecological processes at different scales, even in multiple scale studies, appears to vary between examples (Durance et al 2006) because of different biotic and abiotic conditions in each case. However, according to the variogram modeling results, the relative importance of both multiple scales and multiple scale spatial variation can be structured by nested variogram models related to the stream's features and fish distributions However, fish require different habitats during their life cycle, often migrating long distances to reach sites for feeding, spawning, and early development.…”
Section: Multiple Scales Of Seasonal Fish Densitymentioning
confidence: 97%
“…The lack of spatial independence in ecological data has typically been viewed as obscuring an understanding the biology of organisms under study (Liebhold and Gurevitch 2002). Stream systems can be described hierarchical subsystems and exhibit variation on multiple scales and can help to understand why fish are nested in space and time owing to their ability to respond to biological and physical patterns throughout their life cycles (Frissell et al 1986;Schlosser 1991;Imhoff et al 1996;Allan and Johnson 1997;Maddock 1999;Labbe and Fausch 2000;Li et al 2001; Thompson et al 2001;Fausch et al 2002;Durance et al 2006). Recent studies have demonstrated that stream fish respond to habitat features on a substantially larger scale than previously assumed, primarily owing to movements to various habitats to satisfy the requirements of different life history stages.…”
Section: Introductionmentioning
confidence: 99%
“…Streambed substratum also affects the distribution and abundance of lotic invertebrates (Gurtz & Wallace, 1986). It is generally assumed that the scale at which communities exhibit the greatest variation is the scale over which important physical/chemical gradients or biotic interactions control assemblage composition (Li et al, 2001).…”
Section: Introductionmentioning
confidence: 99%